Accounting from a Cross-Cultural Perspective - Salman, Asma; Abdul Razzaq, Muthanna G. (IntechOpen, 2018)
Accounting is both an art and science, which governs the communication and processing of the financial information in an organization. Technological advancement is helping the accountants to monitor financial performance in real time. This presents both opportunities and challenges for the current day organizations and accounting professionals alike. This book shows many different aspects to the same accounting principles but from a cross-cultural perspective. The diversity of the authors who contributed to this book signify the importance of accounting from various dimensions while ensuring that standards are adhered to, and principles are followed and applied. This book intends to feature the journey from the double-entry bookkeeping developed in medieval Europe to the changing dynamics of accounting. It is divided into five main sections: The Matching Principle, Ethics in Accounting, Insurance Contracts, Green Accounting, and Financial Instruments.